Soil-water characteristic curves of sands by evaporation method - Lee, Yong Wei (Nanyang Technological University, 2023)
Soil-water characteristic curve (SWCC) is an essential unsaturated soil property. It is a relationship of water content of the soil to suction. There are several different laboratory testing methods to develop SWCC. For sand, the Tempe cell is commonly used to determine the SWCC and the range of suction of the SWCC for sand is 0-100 kPa. The Tempe cell is based on the axis- translation method where air pressure is applied to the soil specimen that sits on a high-air entry ceramic disk where water pressure below the ceramic disk is maintained at atmospheric pressure. The soil specimen reaches matric suction equilibrium when its weight remains constant. In this study, the SWCC of sand was determined by using the Tempe cell and also the evaporation method. In the evaporation method, low-cost moisture sensors and a small-tip tensiometer were used to obtain real-time data of water content and matric suction. The SWCC from the evaporation method is compared with SWCC from Tempe cell. The comparison shows that low-cost resistive moisture sensors are more reliable than low-cost capacitive sensors. The SWCCs of fine and coarse sands determined from the evaporation method are comparable to the SWCCs determined from the Tempe cell method.